2000
DOI: 10.1038/sj.bmt.1702164
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of viruses from stools in stem cell transplant recipients: a prospective surveillance study

Abstract: Summary:We prospectively examined stool specimens for enteric viruses in 75 stem cell transplant recipients (autologous 48, allogeneic 27) to determine the frequency and significance of these infections. Only six patients (8%) had a positive isolate. Five of these were allograft recipients (18%) compared to one autograft recipient (2%) (P = 0.02). Unrelated donor BMT recipients were at the highest risk for a viral isolate (OR = 10.5). Adenovirus was the commonest isolate (four patients). One patient each had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…This is consistent with earlier reports. [18][19][20] In conclusion, this retrospective review showed no increase in infection risk following either one or two cycles of mobilizing chemotherapy prior to SCT. The extra weeks of neutropenia also did not alter the incidence of infection following SCT.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with earlier reports. [18][19][20] In conclusion, this retrospective review showed no increase in infection risk following either one or two cycles of mobilizing chemotherapy prior to SCT. The extra weeks of neutropenia also did not alter the incidence of infection following SCT.…”
Section: Discussionmentioning
confidence: 99%
“…The viruses found (rotavirus, adenovirus, astrovirus and CMV) are well recognized as causes of diarrhea in BMT patients. 14,17 The mean day of onset was day þ 25. This fairly late onset may simply represent prolonged hospitalization with iatrogenic exposure, other unknown confounders or merely a chance observation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the published data regarding these complications comes from adult studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] A paucity of information exists in the published literature regarding the incidence, range and severity of gastrointestinal (GI) complications in pediatric patients in the immediate post-BMT period. 19,20 The majority of the pediatric studies examined specific complications such as veno-occlusive disease (VOD), acute pancreatitis or typhilitis in fairly homogeneous patient populations.…”
mentioning
confidence: 99%
“…[8][9][10][11] The only patient who had enterovirus isolated from stool samples during a diarrhoeal episode had GVHD of the gut as well and the role of enterovirus in causing diarrhoea was not clear. 13 The more serious complications of enterovirus infections, such as CNS and cardiac involvement, were not documented in any of the patients. All the CSF, pericardial and pleural fluids obtained during this period were subjected to viral culture and RT-PCR, but no enteroviruses were detected.…”
Section: Discussionmentioning
confidence: 99%